KUALITAS PRAMUWISATA BERLISENSI DI KOTA PEKANBARU - Nur Albania; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find out how the quality of the tour guide licensed in the City of Pekanbaru is viewed from the angle of knowledge.This research uses the method of deskriptif kualitatif for analyzing problems in the lift. As for the sample in this research as much as 8 people consists of the Set of tour Guide in Indonesia Council Representative Area of The diyala province, Riau, Service Culture and Tourism City of Pekanbaru, Travel agent Tour, as well as 4 the tour guide licensed in the City of Pekanbaru. The sample in this research using purposive sampling, Whereas the technique of gathering data in this research using interviews and documentation. With dimensions on the quality of the pramuwisata from the angle of knowledge (Kesrul, 2004:16) composed of 4 kinds of that State of Nature, History, Artificial Environment, as well as Events or New Things Warm Talk about.Based on the results of the research that's been done, seen that the quality of the tour guide licensed in the City of Pekanbaru from the angle of knowledge is still low and need to be improved again.Keywords :Tour Guide, Knowledge of Tour Guides, the Quality of the tour Guide Licensed In the City of Pekanbaru